The Cognitive Effects of Radiotherapy for Brain Metastases - Lehrer, Eric J.; Jones, Brianna M.; Dickstein, Daniel R.; Green, Sheryl; Germano, Isabelle M.; Palmer, Joshua D.; Laack, Nadia; Brown, Paul D.; Gondi, Vinai; Wefel, Jeffrey S.; Sheehan, Jason P.; Trifiletti, Daniel M. (Frontiers in Oncology, 2022)
Brain metastases are the most common intracranial neoplasm and are seen in upwards of 10-30% of patients with cancer. For decades, whole brain radiation therapy (WBRT) was the mainstay of treatment in these patients. While WBRT is associated with excellent rates of intracranial tumor control, studies have demonstrated a lack of survival benefit, and WBRT is associated with higher rates of cognitive deterioration and detrimental effects on quality of life. In recent years, strategies to mitigate this risk, such as the incorporation of memantine and hippocampal avoidance have been employed with improved results. Furthermore, stereotactic radiosurgery (SRS) has emerged as an appealing treatment option over the last decade in the management of brain metastases and is associated with superior cognitive preservation and quality of life when compared to WBRT. This review article evaluates the pathogenesis and impact of cranial irradiation on cognition in patients with brain metastases, as well as current and future risk mitigation techniques.